2001
DOI: 10.1210/endo.142.5.8118
|View full text |Cite
|
Sign up to set email alerts
|

Prolactin-Releasing Peptide as a Novel Stress Mediator in the Central Nervous System*

Abstract: A1/A2 noradrenergic neurons in the medulla oblongata are well known to mediate stress signals in the central nervous system. Stress activates A1/A2 noradrenergic neurons, and then noradrenaline (NA) stimulates ACTH secretion through hypothalamic CRH. On the other hand, PRL-releasing peptide (PrRP) was recently isolated and was found to be produced by some A1/A2 neurons and the dorsomedial hypothalamic nucleus. We previously demonstrated that PrRP neurons make synapse-like contact with hypothalamic CRH neurons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
58
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 86 publications
(67 citation statements)
references
References 37 publications
9
58
0
Order By: Relevance
“…ICV injection of PrRP has been shown to increase plasma ACTH [3, 10]. We have investigated this further by showing this action may occur via the PVN and exploring the possible hypothalamic mechanism of PrRP’s action on plasma ACTH levels.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…ICV injection of PrRP has been shown to increase plasma ACTH [3, 10]. We have investigated this further by showing this action may occur via the PVN and exploring the possible hypothalamic mechanism of PrRP’s action on plasma ACTH levels.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that PVN injection of PrRP rapidly increased ACTH and this effect was maintained for the 40-min duration of the experiment. It is interesting to note that the activation of PrRP neurons by restraint stress, as demonstrated by c-fos expression, is maintained over 6 h [10], which could suggest that PrRP is important in the long-term control of HPA activation in response to stress.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…An icv injection of PrRP also stimulates prolactin [20], ACTH and β-endorphin secretion through a CRHmediated mechanism in the rat [17]. Furthermore, it has been demonstrated that various types of stress, such as restraint and footshock, activate c-Fos accumulation in PrRP neurons in the medulla oblongata in the rat [21][22][23]. …”
mentioning
confidence: 98%